1992
DOI: 10.2307/3587009
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Speech Modification, Prior Knowledge, and Listening Proficiency on EFL Lecture Learning

Abstract: This study investigates the listening comprehension of 388 high-intermediate listening proficiency (HILP) and low-intermediate listening proficiency (LILP) Chinese students of English as a foreign language. These students listened to a lecture, the discourse of which was (a) familiar-unmodified, (b) familiar-modified, (c) unfamiliar-unmodified, or (d) unfamiliar-modified. The modified discourse contained information redundancies and elaborations. After the lecture, the EFL subjects took a multiple-choice exam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
130
5
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(153 citation statements)
references
References 54 publications
11
130
5
1
Order By: Relevance
“…These forms differ in the complexity of their syntax and the psychological salience of their semantic relationship with the initial information. Simple repetition, using the exact same word(s) as stated earlier, is the least complex and most salient form, while giving a synonym is more complex and less salient (Chaudron, 1983;Chiang & Dunkel, 1992). The complexity and saliency of the redundancy form can affect how redundancy impacts L2 listening comprehension.…”
Section: Redundancymentioning
confidence: 99%
See 1 more Smart Citation
“…These forms differ in the complexity of their syntax and the psychological salience of their semantic relationship with the initial information. Simple repetition, using the exact same word(s) as stated earlier, is the least complex and most salient form, while giving a synonym is more complex and less salient (Chaudron, 1983;Chiang & Dunkel, 1992). The complexity and saliency of the redundancy form can affect how redundancy impacts L2 listening comprehension.…”
Section: Redundancymentioning
confidence: 99%
“…This finding is consistent with Chaudron's (1983) finding that redundancy in the form of exact repetition (low syntactic complexity and high psychological saliency) is beneficial for both lower-and higher-proficiency listeners. Chiang and Dunkel (1992) explored the effects of redundancy presented in the form of paraphrasing ("The food of the Pennsylvania Dutch Country is very hearty and delicious. Hearty and delicious food is nourishing and tasty," p. 354), which is more complex than exact repetition (Chaudron, 1983), and found that this redundancy improved comprehension 16 The results for type of redundancy and its interaction with proficiency indicate that more transparent types of redundancy (e.g., exact repetition) are beneficial for lower-proficiency listeners, while higher-proficiency listeners can also benefit from more complex forms of redundancy like paraphrase.…”
Section: Comprehension Items 14mentioning
confidence: 99%
“…For the analysis of L2 listening in natural situations, however, it is far from directly applicable. On the other hand, there are claims that most important of all in the L2 situation is the use of context; efficient use of context enables L2 listeners to compensate for imperfections in lower-level processing (e.g., Chiang and Dunkel, 1992;Long, 1990). This too is an important research topic (indeed, not only in L2 listening); but this too fails to provide a useful analysis of L2 listening and its problems.…”
Section: Introductionmentioning
confidence: 99%
“…Hayati (2010) identifies elements that can affect engagement with listening materials in English language: rate of speech is crucial as ESL learners typically find it difficult to process the fast pace of speech by native English speakers (Hayati, 2010). The choice of topic also is relevant to listening comprehension, as students will be less able to comprehend English-language discussion of topics or subject matter with which they are unfamiliar (Chiang & Dunkel, 1992). As mentioned previously, and as it relates to the decision whether or not to use a grammatically-based ESL instruction approach, listening materials are found by some researchers to be more motivating for students than reading and writing materials (Hayati, 2010; Boekaerts & Niemivirta, 2000).…”
Section: Focusing On Enhancing Listening Skillsmentioning
confidence: 99%